2016
DOI: 10.1016/j.scitotenv.2016.06.093
|View full text |Cite
|
Sign up to set email alerts
|

Brominated and organophosphate flame retardants in indoor dust of Jeddah, Kingdom of Saudi Arabia: Implications for human exposure

Abstract: Different flame retardants (FRs) namely polybrominated diphenyl ethers (PBDEs), emerging brominated/chlorinated flame retardants (Br/Cl FRs), and organophosphate FRs (OPFRs) were analyzed in cars, air conditioner (AC) filters and floor dust of different households from Jeddah, Kingdom of Saudi Arabia (KSA). To the best of our knowledge, this is first study in literature reporting emerging Br/Cl FRs and OPFRs in AC filter dust and also first to report on their occurrence in dust from KSA. Chlorinated alkyl phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 51 publications
7
48
1
Order By: Relevance
“…Similarly, mean concentrations of the 7 individual OPs and the resultant P 7OPs in the 53 indoor dust samples in the present study were lower than those in previously reported data. For example, TBEOP (406 ng/g) in the present study was comparable to levels reported in Guangzhou (Ali et al 2013), Saudi Arabia (Ali et al 2016), and Germany (Brommer et al 2012), although it was much lower than levels found in Beijing (8544 ng/g; Wu et al 2016), Kuwait (10 685 ng/g; Ali et al 2013), Norway (12 800 ng/g; Cequier et al 2014), Sweden (5700 ng/g; Luongo and € Ostman 2016), and the United States (11 000 ng/g; Dodson et al 2012). To the best of our knowledge, significantly high levels of TBEOP were found in Japan (248 521-508 320 ng/g; Araki et al 2014;Mizouchi et al 2015), which were 2 to 3 orders of magnitude higher than in other countries.…”
Section: Concentration Of Ops In Indoor Dustsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, mean concentrations of the 7 individual OPs and the resultant P 7OPs in the 53 indoor dust samples in the present study were lower than those in previously reported data. For example, TBEOP (406 ng/g) in the present study was comparable to levels reported in Guangzhou (Ali et al 2013), Saudi Arabia (Ali et al 2016), and Germany (Brommer et al 2012), although it was much lower than levels found in Beijing (8544 ng/g; Wu et al 2016), Kuwait (10 685 ng/g; Ali et al 2013), Norway (12 800 ng/g; Cequier et al 2014), Sweden (5700 ng/g; Luongo and € Ostman 2016), and the United States (11 000 ng/g; Dodson et al 2012). To the best of our knowledge, significantly high levels of TBEOP were found in Japan (248 521-508 320 ng/g; Araki et al 2014;Mizouchi et al 2015), which were 2 to 3 orders of magnitude higher than in other countries.…”
Section: Concentration Of Ops In Indoor Dustsupporting
confidence: 87%
“…For the 3 chlorinated OPs, the average concentrations for each chemical were lower than those found in Guangzhou and Beijing (except for TDCIPP; He et al 2015;Wu et al 2016). The TCEP concentration (725 ng/g) was similar to levels reported in Saudi Arabia (Ali et al 2016), Kuwait (Ali et al 2013), Belgium (Van den Eede et al 2011), and Romania ) but lower than the levels in the United States (Dodson et al 2012) and several European countries (Bergh et al 2011;Brommer and Harrad 2015;Cristale et al 2016;Luongo and € Ostman 2016). The TCIPP concentration (432 ng/g) was comparable to levels reported in New Zealand and Germany (Brommer et al 2012), whereas the TDCIPP concentration was comparable to that reported in Romania and The Netherlands (Brandsma et al 2014) but lower than concentrations in most of the countries mentioned in this paragraph.…”
Section: Concentration Of Ops In Indoor Dustsupporting
confidence: 83%
“…Unfortunately, OPFRs in various materials can be released into the environment over time via abrasion and/or volatilization, because they are used as additives, and are not bound to the material . An increasing number of studies have found OPFRs in different environmental media, including indoor air, dust, precipitation, outdoor air, arctic air, and soil . In addition, recent studies have documented OPFRs and their metabolites in human breast milk, urine, hair and nails, and the placenta …”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate flame retardants seem to be the dominant flame retardant in indoor dust, with concentrations exceeding those of polybrominated diphenyl ethers (PBDEs) . Despite being less likely to bioaccumulate than PBDEs, OPFRs, especially chlorinated organophosphate flame retardants (Cl‐OPFRs), are considered to be persistent pollutants, because of their resistance to degradation .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been increasing concerns about emerging flame retardants (FRs) and polybrominated diphenyl ethers (PBDEs) due to their recalcitrant persistence and bioaccumulation behaviors in the air (He et al, 2018). According to Ali et al (2016a), average exposure levels to organophosphate FRs in indoor cars, air conditioning filters, and household floors in Jeddah were recorded to be 10,500, 15,400, and 3750 ppb, respectively. From the study, penta-PBDEs, decabromodiphenylethane (DBDPE), and chlorinated alkyl phosphate were identified as the most common indoor chemicals within the three indoor microenvironments.…”
Section: Air Pollutants In Ksamentioning
confidence: 99%